2015
DOI: 10.17795/modernc.8672
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Planned Behavior Theory-Based Education on Female Students’ Obesity-Related Behaviors

Abstract: Background: Adolescence is associated with rapid changes in behavioral patterns, which predispose adolescents to high-risk behaviors, such as immobility and unhealthy eating habits. This study was undertaken to evaluate the impact of an educational intervention based on the Theory of Planned Behavior on high-school female students' obesity-related behaviors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
2
1
0
2
Order By: Relevance
“…The present study demonstrated a positive shift in attitudes toward healthy eating in the intervention group compared to the control group. which is consistent with various studies based on TPB among students [33,[37][38][39][40][41]. In another study among students with dietary behavior in India, intervention with 2 sessions of 1 hour each per class showed signi cantly increased attitude scores in 15 days (paired t-test I=-15.51, p<0.01, C=1.517, p=0.131) [42].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The present study demonstrated a positive shift in attitudes toward healthy eating in the intervention group compared to the control group. which is consistent with various studies based on TPB among students [33,[37][38][39][40][41]. In another study among students with dietary behavior in India, intervention with 2 sessions of 1 hour each per class showed signi cantly increased attitude scores in 15 days (paired t-test I=-15.51, p<0.01, C=1.517, p=0.131) [42].…”
Section: Discussionsupporting
confidence: 89%
“…The intervention signi cantly increased the intention for healthy eating in the intervention group compared to the control group (p<0.001). Notably, similar ndings were observed in studies by [39,45,46], where intervention groups showed signi cantly higher intention scores for healthy eating compared to controls (p<0.001). Likewise, Tsorbatzoudis found that a TPB-based intervention, including posters and lectures promoting healthy eating, led to more positive intentions in the treatment group compared to the control group (p<0.001) [43].…”
Section: Discussionsupporting
confidence: 86%
“…For example, Jejhooni et al (2022) reported that before the educational intervention, no significant difference was found in the behavioural intention between the experimental group and control group; after six months of the training intervention, a significant increase was found in each of the TPB constructs, weight and BMI among the intervention group whereas the control group did not differ significantly after the educational intervention [47]. This has been concluded by Sanaeinasab et al (2020), Mazloomy-Mahmoodabad et al (2017) and Soorgi, Miri and Sharifzadeh (2015), revealing significant changes after educational intervention in behavioural intentions and BMI levels specifically towards the experimental group [48][49][50].…”
Section: Discussionmentioning
confidence: 78%
“…Hasil penelitian tersebut sejalan dengan penelitian yang dilakukan pada siswi yang mengalami obesitas, bahwa terdapat perbedaan sikap sesudah (p<0,001) edukasi pada kelompok kontrol dan perlakuan [16] .…”
Section: Hasil Dan Pembahasanunclassified
“…Melalui metode brainstorming maka ditemukan strategi untuk membatasi fast food, sehingga responden semakin merasa sanggup untuk membatasi fast food, dengan demikian maka terjadi perubahan PBC. Berdasarkan hasil penelitian mengenai edukasi pengaturan diet pada siswi obesitas bahwa terdapat perubahan perceived behavioral control (p<0,001) setelah dilakukan edukasi, perubahan PBC dilakukan melalui kegiatan belanja bahan-bahan makanan rendah kalori sebagai upaya penurunan masalah obesitas, dengan kegiatan belanja maka responden akan yakin mengkonsumsi makanan rendah kalori hasil belanjanya [16] . Hasil penelitian tersebut sejalan dengan penelitian yang dilakukan pada remaja perempuan preventive nutritional sebagai upaya pencegahan diabetes tipe-2 yang menunjukkan bahwa terdapat perbedaan perceived behavioral control (p<0,001) sebelum dan sesudah edukasi pada kelompok perlakuan [15] .…”
Section: Hasil Dan Pembahasanunclassified